S122 Long-term survival and safety with selexipag in patients with pulmonary arterial hypertension: results from the GRIPHON study and its open-label extension. (December 2018) - Coghlan, JG; Galiè, N; Gaine, S; Channick, R; Ghofrani, H-A; Hoeper, M; Lang, I; McLaughlin, V; Preiss, R; Rubin, L; Shiraga, Y; Simonneau, G; et al.
Abstract : Introduction: Pulmonary arterial hypertension (PAH) is a progressive disease with a poor prognosis. In the event-driven GRIPHON study, selexipag significantly reduced the risk of a composite primary endpoint event of morbidity/mortality compared with placebo. Purpose: The long-term safety, tolerability and survival for patients treated with selexipag in the GRIPHON double-blind (DB) study and its open-label extension (OLE) are presented. Methods: All patients that received selexipag in the GRIPHON DB study and/or the OLE were included. Patients were followed for adverse events (AEs) and survival from selexipag initiation until the end of treatment (up to 30 days after selexipag discontinuation for survival), or until the cut-off date (20 December 2017). Results: At the cut-off date, 953 patients had received selexipag during the DB study and/or the OLE. Of the 574 patients randomised to DB selexipag, 330 entered the OLE and continued to receive selexipag (of these, 67 had experienced a morbidity event). A further 379 patients switched from placebo to selexipag in the OLE (160 of whom had experienced a morbidity event). At selexipag initiation, the majority of patients were <65 years old (83.4%), predominantly female (80.8%), and in WHO functional class II (43.7%) or III (50.2%). The median (Q1, Q3) exposure to selexipag was 135.57 weeks (48.57, 228.14) (equivalent to 2561 patient-years). Kaplan-Meier survival estimates at 1, 2, 3 and 5 years were 92.1%, 86.4%, 80.8% and 72.9%, respectively (figure 1); 180 patients had been receiving selexipag for at least 5 years. During the observation period, the proportion of patients with at least one AE or serious AE was 99.4% and 56.7%. The most frequently reported AEs (headache 67.4%, disease progression 44.5%, diarrhoea 44.3%), were related to underlying disease and/or known prostacyclin-related effects; after adjusting for exposure, the incidence per patient year for these AEs was 0.42, 0.28 and 0.25, respectively. The proportion of patients with AEs leading to treatment discontinuation was 31.8%. Conclusion: These analyses are based on a large and comprehensive cohort of PAH patients and provide 5 year survival data (survival rate 72.9%). These analyses also support the known safety and tolerability profile of selexipag. Please refer to page A265 for declarations of interest related to this abstract.